Marketing a food marketing case study - Harding, Ben; Video Education Australasia (Australia : Video Education Australasia, 2002)
A case study of the marketing practices of Cadbury Schweppes, one of the world's largest food & beverage brands. Focuses especially on the four key elements of marketing: product, price, place, and promotion
Title from title screen
DVD format
Keywords: Cadbury Schweppes -- Marketing; Food industry and trade -- Marketing -- Case studies; Beverage industry -- Marketing -- Case studies